The printing revolution in early modern Europe - Eisenstein, Elizabeth L. (Cambridge : Cambridge university press, 2005)
Although the importance of the advent of printing for Western civilisation has long been recognised, it was Professor Eisenstein, in her monumental, two-volume work, The Printing Press as an Agent of Change, who provided the first full-scale treatment of the subject. This illustrated and abridged edition of Professor Eisenstein's study gives a stimulating survey of the communications revolution of the fifteenth century. It begins with a discussion of the general implications of the introduction of printing, and then explores how the shift from script to print entered into the three major movements of early modern times: the Renaissance, the Reformation, and the rise of modern science.
Includes bibliographical references (p. 279-292) and index.
Keywords: Printing -- History. -- Europe; Printing -- Social aspects -- History. -- Europe; Technology and civilization; Europe -- Intellectual life